MDM2 inhibition improves cisplatin-induced renal injury in mice via inactivation of Notch/hes1 signaling pathway. (February 2021) - Luo, X; Zhang, L; Han, G-D; Lu, P; Zhang, Y
Objective: To explore the potential function of MDM2-mediated Notch/hes1 signaling pathway in cisplatin-induced renal injury. Methods: The acute renal injury models of mice after intraperitoneal injection of cisplatin in vivo, and the apoptotic models of human renal tubular epithelial (HK-2) cells induced by cisplatin in vitro, were conducted respectively. The renal function-related parameters were measured. The renal tissue pathological changes and apoptosis were observed by PAS staining and TUNEL staining, respectively. Cell viability and apoptosis were detected by MTT and flow cytometry. Notch/hes1 pathway-related proteins were tested by Western blotting. Results: After mice injected by cisplatin, the levels of Cr, BUN, urine cystatin C, urine NGAL and urine ACR were increased and GFR was decreased with the elevation of renal tubular injury scores, the upregulation of the expressions of MDM2, N1ICD, Hes1 and Cleaved caspase-3, as well as the enhancement of cell apoptosis accompanying decreased ratio of Bcl-2/Bax. However, these cisplatin-induced renal injuries of mice have been improved by MDM2 inhibition. Besides, the declined viability, increased cytotoxicity, and enhanced apoptosis were observed in cisplatin-induced HK-2 cells, with the activated Notch/hes1 pathway. Notably, the phenomenon was alleviated in cisplatin-induced HK-2 cells transfected with MDM2 shRNA, but was severer in those co-treated with AdMDM2. Moreover, Notch1 siRNA can reverse the injury of AdMDM2 on HK-2 cells. Conclusion: Inhibiting MDM2 could reduce cell apoptosis through blocking Notch/hes1 signaling pathway, thus alleviating the acute renal injury caused by cisplatin.